Landscape as a Benchmark: Poetics of Place as a Critical Tool in W.H. Auden’s Prose - Vít, Ladislav (American & British Studies Annual, 2018)
W.H. Auden had a profound and clearly defined spatial awareness. As an editor of anthologies, Professor of Poetry at Oxford and author of essays, reviews, forewords and introductions, he was also prolific in the profession of a literary critic judging the work of others. This paper traces the connections between these two facets, with a special emphasis on Auden’s readiness to use other writers’ topophilic responsiveness to the physical environment and landscape as a benchmark for assessing their qualities. Focusing on Auden’s critical assessment of Wordsworth, Frost, Betjeman and Rilke on the basis of their poetics of place, the present study examines Auden’s implementation of this criterion in his critical method.